A Novel Homozygous Mutation in FOXC1 Causes Axenfeld Rieger Syndrome with Congenital Glaucoma - Micheal, Shazia (PLoS One, 2016)
BACKGROUND: Anterior segment dysgenesis (ASD) disorders are a group of clinically and genetically heterogeneous phenotypes in which frequently cornea, iris, and lens are affected. This study aimed to identify novel mutations in PAX6, PITX2 and FOXC1 in families with anterior segment dysgenesis disorders. METHODS: We studied 14 Pakistani and one Mexican family with Axenfeld Rieger syndrome (ARS; n = 10) or aniridia (n = 5). All affected and unaffected family members underwent full ophthalmologic and general examinations. Total genomic DNA was isolated from peripheral blood. PCR and Sanger sequencing were performed for the exons and intron-exon boundaries of the FOXC1, PAX6, and PITX2 genes. RESULTS: Mutations were identified in five of the 15 probands; four variants were novel and one variant was described previously. A novel de novo variant (c.225C>A; p.Tyr75*) was identified in the PAX6 gene in two unrelated probands with aniridia. In addition, a known variant (c.649C>T; p.Arg217*) in PAX6 segregated in a family with aniridia. In the FOXC1 gene, a novel heterozygous variant (c.454T>C; p.Trp152Arg) segregated with the disease in a Mexican family with ARS. A novel homozygous variant (c.92_100del; p.Ala31_Ala33del) in the FOXC1 gene segregated in a Pakistani family with ARS and congenital glaucoma. CONCLUSIONS: Our study expands the mutation spectrum of the PAX6 and FOXC1 genes in individuals with anterior segment dysgenesis disorders. In addition, our study suggests that FOXC1 mutations, besides typical autosomal dominant ARS, can also cause ARS with congenital glaucoma through an autosomal recessive inheritance pattern. Our results thus expand the disease spectrum of FOXC1, and may lead to a better understanding of the role of FOXC1 in development.